Strategic Learning Management: A Deep Learning Framework with Performance Standardization for Elementary School Success - Lisa Virdinarti Putra; Rina Purwanti; Ratih Laily Nurjanah; Sisca Septiani (Proceeding International Collaborative Conference on Multidisciplinary Science, 2026)
The implementation of deep learning in elementary schools continues to face significant challenges, particularly in strategic learning management and the availability of standardized assessment instruments capable of validly measuring higher-order thinking skills. This study aims to develop a strategic learning management model based on deep learning integrated with standardized assessment instruments to enhance elementary school students' analytical, evaluative, and creative thinking abilities. A mixed-methods approach was employed involving 240 students from eight elementary schools. Data were collected through cognitive tests, questionnaires, classroom observations, and document analysis, and were analyzed using student cognitive achievement tests, Repeated Measures Analysis of Variance (ANOVA), and Structural Equation Modeling (SEM). The findings indicate that the proposed model significantly improved students' deep learning competencies, with a 37.0% increase in the experimental group compared with a 12.0% increase in the control group. The developed assessment instrument also demonstrated excellent construct validity and high reliability. Furthermore, teacher readiness, technology integration, and institutional support were identified as the primary factors influencing the successful implementation of the model. These findings contribute a validated strategic learning management model and standardized assessment instrument that support the development of higher-order thinking skills and improve the quality of learning in elementary education.